2019
DOI: 10.21873/cgp.20137
|View full text |Cite
|
Sign up to set email alerts
|

Co-culture With Human Breast Adipocytes Differentially Regulates Protein Abundance in Breast Cancer Cells

Abstract: Background/Aim: Recent research highlights the role of cancer-associated adipocytes (CAA) in promoting breast cancer cell migration, invasion and resistance to therapy. This study aimed at identifying cellular proteins differentially regulated in breast cancer cells co-cultured with CAA. Materials and Methods: Adipocytes isolated from human breast adipose tissue were co-cultured with hormone receptor-positive (MCF-7) or-negative (MDA-MB-231) breast cancer cells using a transwell co-culture system. Proteomes of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 62 publications
1
5
0
Order By: Relevance
“…In the literature, the expression of CPT1A, ABCG1, SREBF1 and LGALS3BP has been associated with obesity (50-54) and linked to various cancers (55)(56)(57)(58)(59)(60)(61)(62), including breast cancer (63-69) adding plausibility to the findings. Indeed, CPT1A was recently found to be up-regulated in co-cultured adipocytes isolated from human breast adipose tissue with hormone receptor-positive or -negative breast cancer cells (70). Altogether, these findings support the notion that BMI is associated with the expression of CPT1A, ABCG1, SREBF1 and LGALS3BP in normal tissue among breast cancer patients.…”
Section: Discussionsupporting
confidence: 71%
“…In the literature, the expression of CPT1A, ABCG1, SREBF1 and LGALS3BP has been associated with obesity (50-54) and linked to various cancers (55)(56)(57)(58)(59)(60)(61)(62), including breast cancer (63-69) adding plausibility to the findings. Indeed, CPT1A was recently found to be up-regulated in co-cultured adipocytes isolated from human breast adipose tissue with hormone receptor-positive or -negative breast cancer cells (70). Altogether, these findings support the notion that BMI is associated with the expression of CPT1A, ABCG1, SREBF1 and LGALS3BP in normal tissue among breast cancer patients.…”
Section: Discussionsupporting
confidence: 71%
“…Emerging evidence suggests that adipocytes participate in intimate mutual and dynamic crosstalk with cancer cells and promote cancer cell migration, invasion and metastasis and drug resistance [ 25 , 46 ]. Influenced by cancer cells, NAs are driven to become CAAs, which are characterized by a fibroblast-like phenotype, reduced differentiation capacity, and the presence of small fat droplets [ 47 ]. In this process of transformation, CAAs gradually lose their differentiation capacity through the downregulation of markers associated with adipose differentiation, such as FABP4 and adiponectin [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Modern top-down and bottom-up MS-based proteomic techniques, especially those based on MALDI-ToF MS and LC–MS/MS, allowed for understanding of proteomic differences between cancer-associated fibroblasts (CAFs) and their normal fibroblast counterpart; the metabolic reprogramming associated with fibroblast activation; the reciprocal metabolic cross-talk between CAFs and cancer cells that involves the identification of CAF-derived proteins which act as regulators of cancer cell proliferation as well as the contribute to the CAFs secretome; these represent some among a long list of other ECM proteins that interact or remodel ECM, which leads to a complex proteomic profile of tumor matrisome [ 127 , 128 ]. To demonstrate the role of cancer-associated adipocytes (CAAs) in breast cancer cell migration, invasion, and resistance to therapy, DEPs in BC cells co-cultured with CAAs isolated from human breast adipose tissue have been identified and quantified using iTRAQ labelling and LC–MS/MS [ 129 ]. Pathway analysis demonstrated that CAAs emphasized a paracrine role in the enrichment of proteins involved in metabolism, ubiquitin proteasome, and purine synthesis.…”
Section: Proteomics-based Investigation Of Dysregulated Proteins Proc...mentioning
confidence: 99%